Pengimbasan Ketahanan Pisang terhadap Penyakit Layu Fusarium dengan Asam Salisilat In Vitro - Suryanti Suryanti; Yufita Dwi Chinta; Christanti Sumardiyono (Jurnal Perlindungan Tanaman Indonesia, 2009)
Salicylic acid (SA) is an important signal in plant defense. It is used as induced resistance agent against Fusarium wilt. An artificial induction was conducted by shaking the shoot groups of banana tissue culture in liquid medium of Murashige-Skoog (MS). MS medium was added with 0 ppm (as control), ⅛ LC50, ¼ LC50, ½ LC50, and LC50 concentration of SA. Alive shoot groups were subcultured for about three months and were acclimated. Resistance test had been conducted in glass house by inoculated six months old banana seedlings with Fusarium oxysporum f.sp. cubense (Foc). Leaves symptom were observed based on Leaf Symptom Index (LSI) and corm discoloration based on Rhizome Discoloration Index (RDI). The result of this research showed that induced banana seedlings had higher plant resistance to Fusarium wilt than control.